2016
DOI: 10.1093/ije/dyw035
|View full text |Cite
|
Sign up to set email alerts
|

Maternal underweight and obesity and risk of orofacial clefts in a large international consortium of population-based studies

Abstract: In this largest population-based study to date, we found an increased risk of cleft palate, with or without cleft lip, in class II+ obese mothers compared with normal-weight mothers; underweight mothers may also have an increased risk, but this requires further study. These results also suggest that extremes of weight may have a specific effect on palatal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 38 publications
1
32
0
5
Order By: Relevance
“…Among cases, 1134 had cleft lip only, 2078 had cleft lip with palate, and 1723 had cleft palate only. As reported in prior studies (1, 3), smoking, underweight, and obesity rates were higher among cases than controls.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Among cases, 1134 had cleft lip only, 2078 had cleft lip with palate, and 1723 had cleft palate only. As reported in prior studies (1, 3), smoking, underweight, and obesity rates were higher among cases than controls.…”
Section: Resultssupporting
confidence: 76%
“…We did not control for diabetes because it can be a consequence of obesity. Furthermore, prior work has shown that it did not meaningfully account for the associations of BMI with risk of oral clefts (3). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it was suggested that both overweight and underweight interfere with the process of palatal development [15]. This could be linked to maternal nutritional deficiencies and imbalanced dietary patterns during pregnancy which have been strongly associated with the development of OC.…”
Section: Etiologymentioning
confidence: 99%